Acute Left Internal Carotid Artery and Right Popliteal Artery Occlusion Related to Cisplatin-Gemcitabine Based Chemotherapy - Saman Zafar; Rashmika Potdar; Andrew Tiu; Gabor Varadi; John Leighton (Case Reports in Neurological Medicine)
Objectives. The increased risk of thromboembolic complications with active cancer is well known. We present this case to highlight that chemotherapy may increase the risk of thromboembolic events even further in cancer patients. Methods. We report a case of a 64-year-old male with Diffuse Large B-Cell Non-Hodgkin’s Lymphoma who presented with left-sided headache and right calf pain two weeks after starting Rituximab/Gemcitabine/Cisplatin/Dexamethasone chemotherapy. Neurological examination was normal, but there was an absent right dorsalis pedis pulse. He subsequently developed left vision loss. CT angiogram of the head and neck revealed occlusion of his left internal carotid artery and poor opacification of the left ophthalmic artery. An angiogram of the right leg further revealed acute occlusion of the popliteal artery. Results. The patient underwent intra-arterial Tissue Plasminogen Activator injection to his lower limb and was started on Low Molecular Weight Heparin. His vision gradually recovered with time. His chemotherapy regimen was changed to RICE (Rituximab, Ifosfamide, Carboplatin, Etoposide). Conclusion. Based on literature review, there are numerous similar presentations of arterial thromboembolism in patients on Cisplatin-based chemotherapy. A high index of suspicion for such events should be maintained for patients on chemotherapy presenting with unusual symptoms.